1993
DOI: 10.1159/000211142
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the Avène Spring Water on the Dynamics of Lipids in the Membranes of Cultured Fibroblasts

Abstract: In this preliminary report, dealing with the biological properties of AvÈne spring water, we investigated its effects on membrane properties of cultured human skin fibroblasts used as a model cell system. It is shown that incubation of these cells in the presence of AvÈne spring water brings about an increase in the fluidity of plasma membrane. This effect was evidenced by a decrease in the fluorescence anisotropy of the lipophilic probe diphenylhexatriene and by a 3-fold increase in the lateral diffusion coef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 14 publications
2
15
0
Order By: Relevance
“…Different steps may constitute potential sites of cell perturbation leading to an inhibition of the stimulation: primary interaction of substance P (positively charged) with sialic acid residues (negatively charged) or the cell membrane, IgE receptor-ligand bridging, Ca 2+ entry following activation of membrane phospholipases, etc. These hypotheses are consistent with previous studies showing that Avène water modified changes in the hydrodynamic properties of cell membranes leading to an increase in fluidity [3]. Furthermore, numerous pathological processes, such as atopic eczema and psoriasis, are linked to membrane fluidity abnormalities [16].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Different steps may constitute potential sites of cell perturbation leading to an inhibition of the stimulation: primary interaction of substance P (positively charged) with sialic acid residues (negatively charged) or the cell membrane, IgE receptor-ligand bridging, Ca 2+ entry following activation of membrane phospholipases, etc. These hypotheses are consistent with previous studies showing that Avène water modified changes in the hydrodynamic properties of cell membranes leading to an increase in fluidity [3]. Furthermore, numerous pathological processes, such as atopic eczema and psoriasis, are linked to membrane fluidity abnormalities [16].…”
Section: Discussionsupporting
confidence: 92%
“…In vitro, Avène water inhibits human basophil and mast cell allergen-induced activation [1,2]. Recently, it was shown that incubation of cultured human skin fibroblasts with Avène water increased the fluidity of the plasma membrane suggesting that its primary impact is at this level [3].…”
Section: Introductionmentioning
confidence: 99%
“…Thermal water has been shown to modulate cell membrane fluidity33 and reduce lipid peroxidation23. A previous study also showed that mineral water inhibits lymphocyte proliferation induced by epidermal Langerhans cells19.…”
Section: Discussionmentioning
confidence: 99%
“…In vitro effects of ASW, such as increases in cell membrane fluidity, have already been reported [2] and suggested the capacity of ASW to modulate the immune response. The two other responses in vitro which described inhibition of basophil degranulation [21] and inhibition of rat mast cell histamine release [22] in the presence of ASW agree with clinical prescriptions especially recommended for ASW, i.e.…”
Section: Discussionmentioning
confidence: 88%
“…Although the clinical benefit of some medical spa waters has been established, their mechanisms of action remain completely unclear. Avène spring water (ASW) is a weakly mineralized water, containing some 'essential trace elements' which contribute to preserve the medium osmolarity and also increase the fluidity of the plasma membrane from cultured human skin fibroblasts [2]. Therefore, ASW seems to have an effect at the plasma membrane level suggesting a possible modulation of membrane receptors involved in the signal transduction pathways.…”
Section: Introductionmentioning
confidence: 99%